2015
DOI: 10.1007/s12272-015-0650-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pyrite bioleaching solution of Acidithiobacillus ferrooxidans on viability, differentiation and mineralization potentials of rat osteoblasts

Abstract: Iron pyrite, an important component of traditional Chinese medicine, has a poor solubility, bioavailability, and patient compliance due to a high dose required and associated side effects, all of which have limited its clinical applications and experimental studies on its action mechanisms in improving fracture healing. This study investigated Acidithiobacillus ferrooxidans (A.f)-bioleaching of two kinds of pyrites and examined bioactivities of the derived solutions in viability and osteogenic differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…[ 5 ] Also, many studies show that an appropriate concentration of naringin can enhance the expression of alkaline phosphatase in cells and promote osteogenic transformation. [ 6,12,23 ] The loading of naringin on brushite also turns out to be positive in promoting the ALP activity of osteoblasts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] Also, many studies show that an appropriate concentration of naringin can enhance the expression of alkaline phosphatase in cells and promote osteogenic transformation. [ 6,12,23 ] The loading of naringin on brushite also turns out to be positive in promoting the ALP activity of osteoblasts.…”
Section: Resultsmentioning
confidence: 99%
“…[5] Modern scientific and technological results reveal that a proper amount of pyrite can promote the differentiation of osteoblasts and enhance osteogenic function with better mineralization performance and higher protein expression levels of osteogenesis-related genes. [4,6] Several studies have focused on developing novel bone repair scaffolds with pyrite. The porous PDLLA/pyrite scaffolds with 5 wt% pyrite were proven to stimulate the growth of ROS17/2.8 osteoblasts.…”
mentioning
confidence: 99%
“…Bioleaching, as an eco-friendly and energy-saving process, is widely used in metallurgical processing. It is also utilized for in vitro studies of A. ferrooxidans [ 33 , 34 ]. In our bioleaching experiment, walnut shell powder and its phenolic constituents showed high efficiency for inhibiting the oxidation of pyrite.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were plated at 4.2 × 10 5 cells/well in 6-well plate (Corning, NY, USA). After seeding, cells were exposed to Fe 3+ or Fe 2+ iron donors (FAC and FAS) at 0, 100, 200 and 300 μM for 24, 48, and 72 h. Several studies showed that the expression alteration of osteoblast differentiation markers in different osteoblast cell lines including UMR-106 cells could be observed from 12 to 96 h of treatments, and the alteration of mRNA and protein expression was well correlated [38][39][40][41][42]. After incubation, the cells were collected by washing twice with phosphate buffered saline (PBS) solution and dissolved in TRIzol reagent (Invitrogen, Carlsbad, CA, USA) to extract total RNA.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%